Harnessing sustainable N-doped activated carbon from walnut shells for advanced all-solid-state supercapacitors and targeted Rhodamine B dye adsorption - Husain A.; Ansari K.; Mahajan D.K.; Kandasamy M.; Ansari M.N.M.; Giri J.; Al-Lohedan H.A. (Elsevier B.V., 2025)
This research introduces a novel approach to repurposing walnut shells, an abundant agricultural waste, to synthesize sustainable nitrogen-doped activated carbon (N@AC). The resulting material exhibits remarkable properties suitable for dual applications in high-performance all-solid-state supercapacitors and efficient Rhodamine B dye (RhB) adsorption. In a three-electrode setup, the N@AC electrode exhibits an impressive specific capacitance of 484.6 Fg?1 at 1 Ag?1 and remarkable long-term stability, maintaining 97.4% of its initial performance even after 5000 charge-discharge cycles. Simultaneously, the all-solid-state symmetric supercapacitor configuration (N@AC//N@AC) demonstrates outstanding specific capacitance, registering at 168.8 Fg?1 at 1 Ag?1, accompanied by a favourable rate capability of 67.3% at 10 Ag?1. Notably, the N@AC//N@AC configuration attains a high energy density of 39.8 WhKg?1 at 1 Ag?1. Furthermore, N@AC//N@AC exhibits favourable cyclic stability, retaining 83.91% of its initial capacitance even after 10,000 charge-discharge cycles. Moreover, the adsorption efficiency of N@AC toward RhB is scrutinized, highlighting its efficacy in addressing environmental remediation challenges. The porous architecture and nitrogen functionalities of N@AC play a crucial role in expeditiously eliminating organic pollutants from aqueous solutions, offering a sustainable approach to treating wastewater. Optimal conditions for the highest RhB adsorption are identified: pH 7.2, a contact duration of 180 min, and an initial dye concentration of 20 mgL?1. Thermodynamic evaluations, encompassing the determination of ?H?, ?H?, and ?S?, signify the endothermic and spontaneous nature of the adsorption process. In desorption investigations, it is noted that H2O, employed as an eluting agent, proficiently releases 87.35% of the adsorbed RhB dye. ? 2024 Vietnam National University, Hanoi